Mental Readiness of Women's Volleyball Athletes in Banjarnegara Regency to Face The 2025 Pra-Porprov Event - Adelia Tri Hastuti; Agung Wahyudi (Universitas Negeri Semarang, 2025)
The Banjarnegara Regency Women's Volleyball Team will face the Pre-Porprov Event, which is a reguler sporting event held only once every four years. Currently, the level of mental readiness of the athletes is unknown due to the long gap since the previous regular tournament. In fact, mental readiness is a very important factor in determining an athlete's performance in competition. Thus, the purpose of this study is to determine the mental readiness of athletes in the aspects of motivation, self-confidence, anxiety, and the importance of the team. This study is a quantitative study with a survey design. The analysis used statistical analysis and descriptive exploratory methods. The results of the analysis of the Mental Readiness of Women Volleyball Athletes in Facing the Pre-Porprov Event are included in the